PARTICIPANTS IN EXTRACELLULAR MATRIX DESTRUCTION AS PREDICTORS OF RECURRENCE OF FIBROMATOUS NODES GROWTH - Мария Геннадьевна Николаева; Марина Алексеевна Тимченко; Лариса Александровна Хорева; Александра Юрьевна Скрыльник (Мать и дитя в Кузбассе)
The aim of the research – determination of the role of participants in the destruction of the extracellular matrix in the pathogenesis of relapse of myomatous node growth after previously performed uterine artery embolization.